Keynote Address by Professor Emeritus Anuwar Ali in International Conference on Contemporary Issues in Hospitality, Restaurant and Tourism Management, Jan 2014 - Anuwar Ali (2014)

(untitled)
A keynote address by YBhg Prof Tan Sri Anuwar Ali in International Conference on Contemporary Issues in Hospitality, Restaurant and Tourism Management on 24 January 2014 at Treston International College, Taguig, The Philippines